UKRAINIAN DATABASE AND ATLAS OF LIGHT CURVES OF ARTIFICIAL SPACE OBJECTS - Koshkin, N. I.; Savanevich, V.; Pohorelov, A.; Shakun, L.; Zhukov, V.; Korobeynikova, E.; Strakhova, S.; Moskalenko, S.; Kashuba, V.; Krasnoshchokov, A. (Одеські астрономічні публікації, 2017)
This paper describes the Ukrainian database of long-term photometric observations of resident space objects (RSO). For the purpose of using this database for the outer space monitoring and space situational awareness (SSA) the open internet resource has been developed. The paper shows examples of using the Atlas of light curves of RSO’s for analyzing the state of rotation around the center of mass of several active and non-functioning satellites in orbit.